Development of Thiazolidinedione-Based HDAC6 Inhibitors to Overcome Methamphetamine Addiction - Sharma, Chiranjeev (Int J Mol Sci, 2019)
Thiazolidinedione is a five-membered heterocycle that is widely used in drug discovery endeavors. In this study, we report the design, synthesis, and biological evaluation of a series of thiazolidinedione-based HDAC6 inhibitors. In particular, compound 6b exerts an excellent inhibitory activity against HDAC6 with an IC(50) value of 21 nM, displaying a good HDAC6 selectivity over HDAC1. Compound 6b dose-dependently induces the acetylation level of α-tubulin via inhibition of HDAC6 in human neuroblastoma SH-SY5Y cell line. Moreover, compound 6b efficiently reverses methamphetamine-induced morphology changes of SH-SY5Y cells via regulating acetylation landscape of α-tubulin. Collectively, compound 6b represents a novel HDAC6-isoform selective inhibitor and demonstrates promising therapeutic potential for the treatment of methamphetamine addiction.